2011
DOI: 10.1182/blood-2010-04-202911
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of Plasmodium falciparum malaria in humans: insights from splenic physiology

Abstract: Clinical manifestations of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
337
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 304 publications
(350 citation statements)
references
References 90 publications
8
337
2
3
Order By: Relevance
“…Taken together, these observations strengthen the assumption that subtle but measurable mechanical alterations induce the retention of senescent RBC in the spleen [5]. Measuring the elongation index of circulating RBC is physiologically relevant, requires only small volumes of blood, and provides reproducible, operator-independent results [2]. We agree with Lammers et al that large studies spanning the wide range of diseases associated with impaired splenic function [6] are warranted.…”
Section: Reduced Deformability Of Circulating Erythrocytes: a Marker supporting
confidence: 87%
See 1 more Smart Citation
“…Taken together, these observations strengthen the assumption that subtle but measurable mechanical alterations induce the retention of senescent RBC in the spleen [5]. Measuring the elongation index of circulating RBC is physiologically relevant, requires only small volumes of blood, and provides reproducible, operator-independent results [2]. We agree with Lammers et al that large studies spanning the wide range of diseases associated with impaired splenic function [6] are warranted.…”
Section: Reduced Deformability Of Circulating Erythrocytes: a Marker supporting
confidence: 87%
“…As the spleen mechanically retains altered red blood cells (RBC) [2], blood samples from hyposplenic patients are expected to contain an excess of poorly deformable RBC. We thus used two techniques in our study: rotational ektacytometry (LORCA) and microsphiltration.…”
Section: Reduced Deformability Of Circulating Erythrocytes: a Marker mentioning
confidence: 99%
“…Malarial anemia evolves through extravascular elimination of unparasitized erythrocytes by splenic macrophages, concomitant with bone marrow dysfunction and ineffective erythropoiesis [1][2][3]. Early studies demonstrated a shortened lifespan of platelets [4] and uninfected erythrocytes [5] in non-immune patients with falciparum malaria [6].…”
Section: Introductionmentioning
confidence: 99%
“…A number of potential innate control mechanisms have been suggested. In particular, the mechanical removal of pRBCs by the spleen (8,(15)(16)(17)(18) [or liver (19)] is believed to be a primary mechanism by which the host controls the PMF (12). However, few studies have attempted to directly measure host removal of pRBCs in vivo (13,19).…”
mentioning
confidence: 99%